The Influence of Accessibility, Personal Sales and Interest in the Decision of Use of Micro Business Credits (KUM) and Customer Loyalty (Study on Customer of BANK MANDIRI Sepanjang Kota Sidoarjo) - Sonny Brilliant Candra Negara (LPPM NAROTAMA UNIVERSITY, Indonesia, 2018)
This study aims to determine the effect of accessibility, personal selling, interest rates on micro business credit usage decisions and customer loyalty in independent banks throughout the city of Sidoarjo.Methodology: This type of research is quantitative. The research data are primary data obtained from samples with the number of 100 respondents who are customers of Bank Mandiri throughout the city of Sidoarjo. The sampling technique is done using a questionnaire. The data analysis used is Partial Least Square (PLS). Data is processed using SmartPLS.The results of the study show that accessibility, personal sales, and interest rates are significantly influenced by purchasing decisions and customer loyalty. Given accessibility, personal sales and interest rates that have a significant positive influence and a major contribution to Bank Mandiri's buying and loyalty decisions throughout the city of Sidoarjo. Directions must pay attention to accessibility, personal sales, and interest rates